Failure mode analysis (FMA) for visual-based navigation for UAVs in urban environment - Tabassum, Tarafder Elmi; Petrunin, Ivan; Rana, Zeeshan (UK-Robotics and Autonomous Systems (UK-RAS) Network, 2022)
Visual-based navigation systems for Unmanned Aerial vehicles (UAVs) have become an interesting research area focused on improving robustness and accuracy in the urban environment. However, a lack of integrity can damage UAVs, limiting their potential usage in civil applications. For safety reasons, integrity performance requirements must be met. In literature, such systems require significant attention for their ability to perform fault analysis, referred to as failure mode. In this paper, we have conducted a failure mode analysis in urban environments for UAVs to identify threats and faults presented in existing Visual-inertial Navigation Systems. In addition, we propose a federated-filter-based fault detection and execution system to improve navigation performance under faulted conditions.
Keywords: visual-based navigation; integrity; failure mode analysis; urban environment; GNSS